Tinjauan Kriminologis Tindak Pidana Penganiayaan Berat Terhadap Karyawati Kalbe Farma Di Kota Kupang - kalelena, franklin yulius davidson; Manafe, Deddy R. CH; Dima, Adrianus Djara (Law Faculty, Nusa Cendana University, 2023)
According to the 1945 Constitution of the Republic of Indonesia, Amendment IV Article 1 paragraph (3) which reads